Chest Radiograph Interpretation: A Flipped Classroom Approach - Christopher King; Joseph Sweigart; Nicole Restauri; Nichole Zehnder (Association of American Medical Colleges, 2016)
Abstract Introduction This flipped classroom resource is designed for use within core clinical clerkships to teach third-year medical students a systematic approach to interpreting chest X-rays. The flipped classroom approach was developed in response to student feedback on the previous iteration of this session, which included an interactive PowerPoint presentation. Following this session, students requested more time with practice interpretation during the session. The resource is designed for large groups (15-25 students). Methods This revised approach combines a video for students to watch before the teaching session with a PowerPoint slide deck of cases to work through within the session. The video reviews basic chest anatomy, then introduces the basic A-B-C-D-E-F (airway-bones-cardiomediastinum-diaphragms-effusions-lung fields) framework for reading chest X-rays, giving students the tools needed to systematically approach interpreting chest X-rays before attending the practice session. The PowerPoint slide deck provides several example cases that allow the preceptor to give individual students the opportunity to practice systematic interpretation in the large-group session. Results This resource is used in the third-year inpatient internal medicine clerkship to introduce chest X-ray interpretation on the first day of the rotation. Overall, students rated this session highly, with 100% of students saying they would recommend it to other students. Students also had strong agreement with the following statements on a 5-point Likert scale: "This session gave me a structured approach to interpreting chest X-rays" (4.93/5), "This session increased my ability to recognize patterns on chest X-rays" (4.79/5), and "This session improved my ability and confidence for reading chest X-rays" (4.79/5). Discussion In creating this session, the authors successfully provided students with the language and standardized approach necessary to begin to interpret chest radiographs in the hospital setting. Students are encouraged in the session to compare their interpretations to those provided by the radiologist in the final report.